Investigations on technique and tactics of race walking during Olympic Games Athens 2004 - first announcement - Aschenbrenner, P.; Erdmann, W. S.; Giovanis, V.; Lipinska, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The paper presents preliminary information devoted to the investigations on technique and tactics of race walkers participating at distances of 20 (males and females) and 50 (males) km during Olympic Games Athens 2004. Bipedal walking, the common motor behavior of humans, is complicated in technique. Even more complicated is race walking. In order not to have any flying sequence of a gait cycle walkers use specific technique. Increasing velocity up to a certain level can be done by lengthening of stride, then increasing movement frequency is needed. The latter is difficult if a walker has big moment of inertia of his or her lower extremities. Greater moment of inertia decreases angular velocity. So there should be some compromise between length of lower extremities and their moment of inertia. Cracow researchers gave data on race walking technique based on investigations done on treadmill (Ruchlewicz et al. 2003). It is interesting what the technique looks like during the real competition. Tactics of walking or running and also of any other type of long distance movement should take into account specific distribution of velocity. It is well known the first kilometers shouldn't be run or walked with high velocity. Often the best competitors run a second part of a distance faster than the first one (Gabrys and Celeban 1996, Aschenbrenner 2002, Erdmann 2005, Lipinska 2005). The aim of the research work was to investigate specific technique of walkers and their tactics based on velocity distribution along the course during Olympic Games Athens 2004 competitions. MATERIAL AND METHOD: There were 57 women and 47 men participating in 20 km race and 54 men participating in 50 km race. Race walkers were recorded while they walked on 2 km loop outside the stadium. Two video cameras set perpendicular to each other were used for recording with frequency of 50 Hz.